Assessment of novel halo- and thermotolerant desert cyanobacteria for phycobiliprotein production. (July 2022) - Bounnit, Touria; Saadaoui, Imen; Ghasal, Ghamza Al; Rasheed, Rihab; Dalgamouni, Tasneem; Jabri, Hareb Al; Leroy, Eric; Legrand, Jack
Abstract: Four indigenous cyanobacteria isolates identified as QUCCCM 34: Chroococcidiopsis sp., QUCCCM 54: Pleurocapsa sp., QUCCCM 77: Euhalothece sp., and QUCCCM 129: Cyanobacterium sp. were investigated during this study. Temperatures and salinities observed in outdoor were reproduced indoor, using small-scale photobioreactors, and culture conditions were optimized for maximum biomass and phycobiliprotein productions. The strains showed their halo and thermotolerance capacity. The highest biomass productivity was 125 ± 1.1 mg x L −1 d −1 for Pleurocapsa sp.at 30 °C–40 ppt. The major phycobiliproteins were phycocyanin, and the content was strain and age dependent. Pleurocapsa sp., Euhalothece sp., and Cyanobacterium sp reached their highest phycocyanin content (up to 160 ± 2.6 mgPC gx -1 ) after 4, 8, and 10 days, respectively, while it was only up to 100 ± 3.5 mgPC gx -1 for Chroococcidiopsis sp. at day 4, 40 °C–60 ppt. Increasing temperature and salinity stimulated the phycocyanin synthesis in Chroococcidiopsis sp, Pleurocapsa sp. and Euhalothece sp., whereas only salinity increment enhanced the pigments production(both phycoerythrin and phycocyanin) for Cyanobacterium sp. Finally, all the pigment extracts exhibited an antioxidant and radical scavenging activity which were maximal for the extracts from Pleurocapsa sp., with ≈ 60 mM Trolox equivalent gx −1 and 50%, respectively. Graphical Abstract: ga1 Highlights: Novel cyanobacteria isolates were studied for their thermotolerant and halotolerant ability. Temperature and salinity affected the growth kinetics with highest biomass productivity of 125 ± 1.1 mg x L −1 d −1 for Pleurocapsa sp. The major phycobiliproteins were Phycocyanin (up to 16 %.), and the content was strain and age dependent. Pigment extracts exhibited remarkable antioxidant ability higher than those reported for Spirulina sp.